2010
DOI: 10.5194/acpd-10-26411-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical mass balance estimation of arsenic in atmospheric dust fall out in an urban residential area, Raipur, Central India

Abstract: The components and quantities of atmospheric dust fallout have been reported to be the pollution indicator of large urban areas. The multiplicity and complexity of sources of atmospheric dusts in urban regions has put forward the need of source apportionment of these sources indicating their contribution to specific environmental receptor. The study presented here is focused on investigation of source contribution estimates of Arsenic in urban dust fallout in an urban-industrial area, Raipur, India. Sou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Particulate matter with a size of greater than 10 μm and the ability to settle from the air is the main component of dust fall (Ahmad, 1975;Cadle, 1975;Espinosa et al, 2001;Sami et al, 2006). Dust fall makes a significant contribution when ascertaining pollution in urban areas (Harrison et al, 1997;Xia et al, 2007;Balakrishna et al, 2010), industrial activities and at construction sites (Fuglsang, 2002;Pandey et al, 2008) as well as from vehicle exhaust emissions and soil dust (Arsene et al, 2007). In order to understand regional dust pollution, the dust fall rate and its chemical constituents must first be determined (Harrison, 1986;Pandey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter with a size of greater than 10 μm and the ability to settle from the air is the main component of dust fall (Ahmad, 1975;Cadle, 1975;Espinosa et al, 2001;Sami et al, 2006). Dust fall makes a significant contribution when ascertaining pollution in urban areas (Harrison et al, 1997;Xia et al, 2007;Balakrishna et al, 2010), industrial activities and at construction sites (Fuglsang, 2002;Pandey et al, 2008) as well as from vehicle exhaust emissions and soil dust (Arsene et al, 2007). In order to understand regional dust pollution, the dust fall rate and its chemical constituents must first be determined (Harrison, 1986;Pandey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Three different environments namely, rural (Kosmarra, District Dhamtari), urban (Raipur City, District Raipur) and industrial (Bhilai City, District Durg) have been chosen within an area of 400 km 2 in central India for air sampling program. Three major coal-fired industries (7 Mt steel production, cement manufacturing and 500 MW power generation) are located in the industrial site, which, collectively, emit ~25 tonnes of atmospheric particulate matter every year (Matawle et al, 2014;Guttikunda et al, 2015;Dewangan et al, 2016, Dubey andPervez, 2008;Balakrishna and Pervez, 2009;Balakrishna et al, 2010). Rural site is about 100 km away from both urban and industrial site and free from any major coal-fired industries.…”
Section: Study Area and Air Samplingmentioning
confidence: 99%
“…Similar concentration levels of sulphur in urban and industrial sites might be due to close proximity of both sites (~45 km distance between urban and industrial sites) and emissions from major coal-fired industries are affecting both sites in a uniform scale. As far as source marker species are concern, Ni, V, Cu and Mo are classified as vehicular components; Zn, Pb are known for road dust sources; Ca, Mg, Na and Al represent natural dust components; As, S, and Se indicate coal power plant emission components and Cd, Zn, Cr, Fe and As address other industrial emissions (Cao et al, 2005;Duan et al, 2006;Balakrishna and Pervez, 2009;Balakrishna et al, 2010;Chakraborty and Gupta, 2010;Matawle et al, 2014Matawle et al, , 2015Agarwal et al, 2017;Liang et al, 2018). Day/night variability in PM 2.5 elemental concentrations of urban site (Raipur) has also been investigated.…”
Section: Characterisation Of Elements In Pm 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Massey et al[27] have reported the measurements of indoor PM2.5 in selected households in Agra and recorded maximum average concentration of PM2.5 in rural homes (173.03 µg m -3 ), compared to road side homes (137.93 µg m -3 ) and urban homes (135.55 µg m -3 ) with significant contribution from outdoor infiltration. Balakrishna et al[48] investigated the indoor and outdoor sources of arsenic in urban area of central India. Road traffic has shown higher contribution in indoor and automobile exhaust had shown higher contribution of arsenic.…”
mentioning
confidence: 99%